Enhancing the process of teaching and learning homecare - Hermann,Ana Paula (2018)
ABSTRACT Objective: to identify possibilities for improvement in the process of teaching and learning homecare in nursing, pharmacy, medicine, nutrition, dentistry and occupational therapy courses. Method: qualitative research using the Grounded Theory approach. Sixty-three semi-structured interviews were conducted with students, teachers and graduates of the six mentioned courses at a public university in the south of Brazil. Data analysis was performed through open, axial and selective coding. Results: the possibilities for improving the process of teaching and learning homecare included: scientific production in the area; use of different teaching techniques; development of extracurricular activities; extension projects; curricular reformulation; and laboratory simulation. Final considerations: the strategies cited in this study enable undergraduate courses in health to envisage the possibility of enhance the process of teaching and learning homecare.